1980
DOI: 10.1115/1.3153600
|View full text |Cite
|
Sign up to set email alerts
|

An Explosive Loading Technique for the Uniform Expansion of 304 Stainless Steel Cylinders at High Strain Rates

Abstract: A new explosive loading technique is applied to study the uniform plastic expansion and fracture initiation of 304 stainless steel cylinders. An annular layer of dry PETN high explosive is placed in contact with the inner diameter of the cylinder and surface-initiated with an array of etched copper bridgewires. This technique produces a simultaneous detonation of the explosive and a nearly uniform expansion of the stainless steel cylinders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The generated cylindrically expanding detonation waves were used to examine the dynamic response of steel cylinders at high strain rates of 104 s-1 [4], which is one-order higher strain rate than those in similar studies [6]. Most of the fragmentation models [7] for cylinders are based on axially phased detonation initiated at one end of the cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…The generated cylindrically expanding detonation waves were used to examine the dynamic response of steel cylinders at high strain rates of 104 s-1 [4], which is one-order higher strain rate than those in similar studies [6]. Most of the fragmentation models [7] for cylinders are based on axially phased detonation initiated at one end of the cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the experimental investigations described above used either explosives or projectile to obtain high strain rates; with the exception of the work of Forrestal et al (1980), the radial expansion of the cylinder was nonuniform along the length of the cylinder, either because of nonuniform detonation or because of the nature of the plug development. In fact, in the projectile impact loading, regions away from the center of the cylinder do not experience significant direct loading at all.…”
Section: Introductionmentioning
confidence: 98%
“…Grady (2006) interpreted this observation successfully through Mott's fragmentation model. Forrestal et al (1980) developed an explosive loading technique where a fine grid patterned mesh was used to detonate a PETN charge uniformly; therefore the pressure in the cylindrical specimen evolved uniformly over the entire cylinder, unlike the propagating load in Winter's experiment. wall thickness 0.25;D/t ∼ 20) and demonstrated that nearly uniform strains can be developed in cylindrical specimens; furthermore, they determined that the strain at incipient fracture increased as the thickness of the cylinder increased, but did not report data on fragmentation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation